Performance Evaluation Of Unidirectional Lightweight Encapsulation Using ns-2 And DVB-S Testbed. - Ang, Way-Chuang; Teh, Chee-Hong; Wan, Tat-Chee; Budiarto, Rahmat (2007)
Unidirectional Lightweight Encapsulation (ULE) is a recently published standard to overcome the efficiency problems of Multi-Protocol Encapsulation for satellite data transmission. This paper presents a comparative study of Unidirectional Lightweight Encapsulation performance using ns-2 [ll simulation and a DVB-S testbed. Performance metrics such link utilization packet loss and latency were taken. It was found that the results of both approaches were comparable